Should athletes use their stronger leg on the front block during the sprint start? - Salo, A. I. T.; Gayen, M.; Patterson, J.; Wilson, C. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to understand force production differences Men alternating feet on the starting blocks. The hypothesis was that the dynamically stronger leg should be on the front. Utilising force plates, eight male athletes performed starts alternating the front foot on the block, as well as single leg vertical countermovement jumps to test dynamic strength. In total, 121 starts were analysed. At the group level, there were no statistically significant differences in any of the force variables between dynamically stronger and weaker leg. The results raised some doubts to the theory that the stronger leg should be on the front block during the sprint start. Consequently, the advice for coaches training developing athletes is to allow athletes to use the block settings they feel comfortable with, rather than trying to overanalyse which leg should be on the front or rear block.